2016
DOI: 10.1521/soco.2016.34.2.149
|View full text |Cite
|
Sign up to set email alerts
|

The Tipping Point of Moral Change: When Do Good and Bad Acts Make Good and Bad Actors?

Abstract: Moral and immoral behaviors often come in small doses. A person might donate just a few dollars to charity or cheat on just one exam question. Small actions create ambiguity about when they might reflect a permanent change in an actor's moral character versus simply a passing trend. At what sum of good or bad behaviors do observers believe that others have transformed for better or worse, when their actions begin to reflect "them"? Five experiments reveal that this moral tipping point is asymmetric. People req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 43 publications
3
36
0
Order By: Relevance
“…Participants were asked to indicate how many consecutive instances of the new behavior would need to occur to convince them that the actor's "moral character had transformed" (Klein & O'Brien, 2016, p. 152). Participants perceived negative transformations much quicker than positive transformations, and this was true for commencing negative behaviors and for ceasing positive behaviors (Klein & O'Brien, 2016). A general heightened sensitivity to negative information means that people appear to be quicker to categorize an actor as "bad" (vs.…”
Section: Moral Categorization Involving Unknown Othersmentioning
confidence: 98%
See 2 more Smart Citations
“…Participants were asked to indicate how many consecutive instances of the new behavior would need to occur to convince them that the actor's "moral character had transformed" (Klein & O'Brien, 2016, p. 152). Participants perceived negative transformations much quicker than positive transformations, and this was true for commencing negative behaviors and for ceasing positive behaviors (Klein & O'Brien, 2016). A general heightened sensitivity to negative information means that people appear to be quicker to categorize an actor as "bad" (vs.…”
Section: Moral Categorization Involving Unknown Othersmentioning
confidence: 98%
“…Success in social interactions involves successfully predicting the actions of others (Waytz & Young, 2018). As such, a key goal of moral categorization is to distinguish "good" from "bad" people (Uhlmann et al, 2015), by attempting to identify a person's moral "essence" (e.g., Dunlea & Heiphetz, 2020;Heiphetz & Dunlea, 2019), or "character" (e.g., Klein & O'Brien, 2016;Siegel et al, 2017Siegel et al, , 2018. This enables people to establish relationships or pursue continued interactions with "good" people, and to limit their interactions with "bad" people (or at least treat interactions with "bad" people with caution).…”
Section: Moral Categorization Involving Unknown Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at least two lines of research suggest that individuals may have a non-preference for the potential for a group's moral improvement, but an aversion to the potential for a group's moral decline. The first line includes experiments evaluating beliefs about others' moral improvement and decline, which showed that people's evaluations of moral and immoral behaviors are asymmetric [29][30][31][32][33]. For example, Klein and Epley [33] described a situation in which an accomplished professor who received an $80,000-grant for his research decided to donate $10,000 to a nonprofit institution dedicated to research on poverty; this action was rated as "nice" as donating the whole sum of $80,000.…”
Section: Asymmetric Biases Regarding Potential For Moral Improvement mentioning
confidence: 99%
“…Research shows that people do not force others to become more moral, but they cannot tolerate others becoming more immoral [29]. Consequently, people who perform different degrees of good deeds may be perceived to have the same degree of kindness, but the more bad things they do, the worse they are [31,32]. In addition, bad actions are often more powerful than good ones [43].…”
Section: Plos Onementioning
confidence: 99%